Exertional Myopathy in a Juvenile Green Sea Turtle (Chelonia mydas) Entangled in a Large Mesh Gillnet - Brianne E. Phillips; Sarah A. Cannizzo; Matthew H. Godfrey; Brian A. Stacy; Craig A. Harms (Case Reports in Veterinary Medicine)
A juvenile female green sea turtle (Chelonia mydas) was found entangled in a large mesh gillnet in Pamlico Sound, NC, and was weak upon presentation for treatment. Blood gas analysis revealed severe metabolic acidosis and hyperlactatemia. Plasma biochemistry analysis showed elevated aspartate aminotransferase and creatine kinase, marked hypercalcemia, hyperphosphatemia, and hyperkalemia. Death occurred within 24 hours of presentation despite treatment with intravenous and subcutaneous fluids and sodium bicarbonate. Necropsy revealed multifocal to diffuse pallor of the superficial and deep pectoral muscles. Mild, multifocal, and acute myofiber necrosis was identified by histopathological examination. While histological changes in the examined muscle were modest, the acid-base, mineral, and electrolyte abnormalities were sufficiently severe to contribute to this animal’s mortality. Exertional myopathy in reptiles has not been well characterized. Sea turtle mortality resulting from forced submergence has been attributed to blood gas derangements and seawater aspiration; however, exertional myopathy may also be an important contributing factor. If possible, sea turtles subjected to incidental capture and entanglement that exhibit weakness or dull mentation should be clinically evaluated prior to release to minimize the risk of delayed mortality. Treatment with appropriate fluid therapy and supportive care may mitigate the effects of exertional myopathy in some cases.